2022
DOI: 10.47936/encephalitis.2022.00080
|View full text |Cite
|
Sign up to set email alerts
|

A case of leucine-rich glioma-inactivated 1 antibody encephalitis with schizophrenia-like symptoms as an initial clinical manifestation

Abstract: Leucine-rich glioma-inactivated 1 (LGI-1) antibody encephalitis is a type of limbic encephalitis characterized by faciobrachial dystonic seizure and short-term memory loss as initial clinical symptoms. We present a case initially misdiagnosed as schizophrenia and finally diagnosed as LGI-1 antibody encephalitis. A 41-year-old female presented to the neurology clinic with a 4-month history of anxiety and disoriented speech and a new onset headache. Her explanation of symptoms was unclear, and she was unable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 14 publications
4
9
0
Order By: Relevance
“…7 Moon et al reported the case of a 41-year-old woman who presented with anxiety for 4 months, followed by hallucinations 6 months later, and was diagnosed with schizophrenia. 8 Taken together, the present and the previous cases indicate diversity in the characteristics, age of onset, and the duration of isolated psychiatric symptoms. [6][7][8] In the present case, the main symptoms at the first visit to our hospital were hallucinations and delusions, and acute psychotic disorder was also a differential diagnosis.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…7 Moon et al reported the case of a 41-year-old woman who presented with anxiety for 4 months, followed by hallucinations 6 months later, and was diagnosed with schizophrenia. 8 Taken together, the present and the previous cases indicate diversity in the characteristics, age of onset, and the duration of isolated psychiatric symptoms. [6][7][8] In the present case, the main symptoms at the first visit to our hospital were hallucinations and delusions, and acute psychotic disorder was also a differential diagnosis.…”
Section: Discussionsupporting
confidence: 68%
“…8 Taken together, the present and the previous cases indicate diversity in the characteristics, age of onset, and the duration of isolated psychiatric symptoms. [6][7][8] In the present case, the main symptoms at the first visit to our hospital were hallucinations and delusions, and acute psychotic disorder was also a differential diagnosis. Anti-NMDA receptor encephalitis tends to develop more frequently in young women and is associated with tumors.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations